Aggregate savings, finance and investment - Fernando J. Cardim de Carvalho (Intervention. European Journal of Economics and Economic Policies, 2012)
Among the areas in which the Keynesian revolution has been more unsuccessful in changing orthodox views, the relationship between savings and investment must certainly be the best known. Even today, after more than seventy years of publication of The General Theory, policy-makers are still advised to raise national savings rates in order to accelerate growth (and, more recently, end the crisis initiated in 2007 in the United States). Keynes?s proposition that investment creates savings, and not the converse, seems to violate fundamental intuitions of economists as well as of the general public. In fact, investment creates savings in monetary economies, the operation of which is harder to grasp than the corn economy that inspires the opposite causality. How is the relationship between savings and investment defined in Keynesian and orthodox theories? In this paper, Keynes's views are contrasted to Wicksell's and to Wicksellian approaches embodied in loanable funds theories. In particular, one searches to clarify the theoretical relationship between the concept of aggregate savings (non-consumed output) and financial savings (net demand for assets) that should be more relevant to a discussion of investment finance. The special concept of finance employed by Keynes is used to stress the role played by banks in Keynes?s theory and, in combination with his rejection of Say's law, to clarify the meaning of the »investment creates saving« proposition.
Keywords: E02; E21; E44; 330; Keynes; Post Keynesian economics; saving and investment